Plan de marketing para el mejoramiento de las ventas de comidas y dulces tradicionales en el Parque Ecológico de Solanda de la Asociación de pequeño comerciantes 10 de Julio ubicada en la ciudad de Quito - Iza Iza, Gabriela Natalia (2015)
The regularization process with the purpose of planning, organizing, and controlling the city has allowed merchants to self-employed are identified, and thus have the right to organize and defend their work in the physical space granted by the Municipality and Administrators Zonal opening the field to new opportunities and a better quality of life. This marketing plan is for the Association “10 de Julio” that is a worthy representative of the struggle and perseverance for the regularization of their members in the city of Quito. This research is based primarily on the need for its members to attract more clientele to their points of sale and to better market their products in the Eco-Park of Solanda. In this plan proposes strategies that would complement the fulfillment and achievement of their goals in a short period of time. With the implementation of the marketing plan seeks to improve the organization, planning, image, personal presentation and products, attracting customers and strategic alliances that will allow you to get an increase in their sales, as that will be representative of your income and growth in the market. The research that has been conducted this structured in an organized and orderly fashion that relates to the analysis of the sector in which it operates the Association as well as the internal requirements that this has, in order to know their current position, which will help to determine the positive and negative aspects and as well develop improvement strategies that reduce the risk, and competitive.